Silent Revolution: Artificial Intelligence Innovation in Students’ Career Interest in Taxation - Bawias, Hizkia Hazael Bezaliel; Yusuf, Rolland M; Paranoan, Selmita (UNKLAB Business School, 2025)
The development of greater artificial intelligence innovation has silenced the accounting profession, including the field of taxation. This study aims to assess the impact of artificial intelligence on students' career interest in taxation using the diffusion of innovation theory. A quantitative approach with the Partial Least Square (PLS) model was applied with an analysis tool using the WarpPLS 7.0 application, then determining the sample based on purposive sampling techniques with a total of 79 student respondents. The results showed that artificial intelligence innovation, artificial intelligence communication channels, and artificial intelligence adoption decisions had a positive and significant effect on students' career interest in taxation. This study found that the role of artificial intelligence affects knowledge and understanding, motivation and assessment of the work environment by students in the field of taxation. The application of artificial intelligence in the lecture process is necessary to understand in real time the risks and opportunities in the utilization of artificial intelligence under the supervision of educators.